COMPARATIVE ANALYSIS OF FARMING VARIETY OF PEANUT NOLION 1 AND NOLION 2 IN THE DISTRICT OF SOUTH TOTIKUM BANGGAI KEPULAUAN - Radia N. Bonenehu; Made Antara; Rustam Abd Rauf (Tadulako University, 2016)
This study aims to: (1) Knowing large farm income peanut varieties Nolion 1 and Nolion 2 in District Totikum South Banggai Islands, and (2) Determine the ratio of production and farm income peanut varieties Nolion 1 and Nolion 2 in District Totikum South Banggai Islands, research type used in this research is descriptive analysis with comparative research method is ex post facto. Sampling is done by simple random sampling method (simple random sampling) take 15% of the population with sampling technique Proportional Stratified Random Sampling. Analysis of data using revenue analysis and comparative analysis / comparison of the average production and average farm income of farmers responder peanut varieties Nolion Nolion 1 and 2. The results show the average farmer's income respondents peanut farmers varieties Nolion 1 in one process location production research Rp 10,073,697- /ha and Rp.10,637,612,-/ha for varieties Nolion 2. The results of comparative analysis (Compare Independent samplest-test) is obtained, there are differences in average production and income of farmers varieties with varieties Nolion 1 and Nolion 2, on the level of α 5%. Conclusion of the study that there is a difference in the average production and average farm income farm Nolion 1 peanut varieties and varieties of peanut farming Nolion 2